Health Financing for the Rural Poor: Findings from a Survey Study - Michael A. Costello; Marilou Costello (Philippine Institute for Development Studies (PIDS), 1995)
This study deals with the health care needs of rural poor in Bukidnon and Misamis Oriental. Focusing on small-scale farmers and fishermen, landless laborers, women-headed households and disadvantaged minority groups, this paper investigates their attitudes and financing behavior towards health care. The present effort may be considered descriptive rather than explanatory/hypothesis testing.
Keywords: 330; rural poor; poverty; health facilities; demographic and location; landless people; rice farm; fertility